THE SINGLE CURRENCY FOR ISLAMIC NATIONS: DO HETEROGENEITIES MATTER? - Agustiar, Memet (Bank Indonesia, 2018)
The purpose of this study is to assess the readiness of 44 OIC member countries to form a currency union and to test whether the Optimum Currency Area (OCA) criteria remain relevant to a large region like the OIC. Large geographic size is subject to socio-economic and geographic disparities. This study employs the OCA-index to estimate the degree of readiness of the OIC to form a currency union. Five selected criteria –business cycle synchronization, trade openness, inflation similarity, the size of the economy, and distance – were employed to determine the OCA using Ordinary Least Squares regression. The findings of this study estimate that 63 percent of pairs of countries in the OIC are ready to form a currency union. The selected OCA’s criteria present the best-fit variable in explaining the OCA for the OIC. This paper verifies that economic and geographic heterogeneities are not the main obstacle to forming a currency union. This study provides an important contribution to the theory of OCA primarily in clarifying the application of the OCA conditions in a large observation like the OIC, which comprises many countries and many blocs.